2004
DOI: 10.1152/jn.01173.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modular Functional Organization of Cat Anterior Auditory Field

Abstract: . Two tonotopic areas, the primary auditory cortex (AI) and the anterior auditory field (AAF), are the primary cortical fields in the cat auditory system. They receive largely independent, concurrent thalamocortical projections from the different thalamic divisions despite their hierarchical equivalency. The parallel streams of thalamic inputs to AAF and AI suggest that AAF neurons may differ from AI neurons in physiological properties. Although a modular functional organization in cat AI has been well documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 68 publications
13
81
0
Order By: Relevance
“…1, 8B). These extrinsic clusters of labeling were focal in each area and, in the tonotopic areas, aligned with CF maps (Imaizumi et al, 2004;Lee et al, 2004b). The major extrinsic input arose from AI (>30%), with other tonotopic fields each providing ~10-20%, and non-tonotopic regions contributing <5% each (Fig.…”
Section: Anterior Auditory Field (Aaf)supporting
confidence: 55%
“…1, 8B). These extrinsic clusters of labeling were focal in each area and, in the tonotopic areas, aligned with CF maps (Imaizumi et al, 2004;Lee et al, 2004b). The major extrinsic input arose from AI (>30%), with other tonotopic fields each providing ~10-20%, and non-tonotopic regions contributing <5% each (Fig.…”
Section: Anterior Auditory Field (Aaf)supporting
confidence: 55%
“…It has been suggested that the AAF in the cat is homologous to the caudomedial (CM) belt area in the primate brain (see de la Mothe et al, 2006 for a discussion of the similarities between the primate CM and cat AAF). Like the primate CM (Recanzone, 2000), both the cat and ferret AAFs have shorter response latencies relative to the A1 and an under‐representation of mid‐frequencies (Imaizumi et al, 2004; Bizley et al, 2005). The AAF in the cat is innervated predominantly by the rostral pole of the MGB and the dorsal division of the MGB, with smaller inputs from the MGBv and MGBm (Imig and Morel, 1983; Morel and Imig, 1987; Lee and Winer, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…The auditory cortex of the cat comprises a number of fields that differ in their anatomical connections (Huang and Winer 2000;Lee and Winer, 2007;Morel and Imig 1987;Rouiller et al 1991) and physiological response properties (Imaizumi et al 2004;Lee et al 2004a, b;Irvine 1981, 1982;Reale and Imig 1980). Three of these fields-the primary (A1), anterior (AAF), and posterior (PAF) auditory fields-receive robust input from the ventral division of the medial geniculate body (MGB) (Morel and Imig 1987;Huang and Winer 2000).…”
Section: Introductionmentioning
confidence: 99%